The Base Excision Repair Pathway in the Nematode Caenorhabditis elegans - Elsakrmy, Noha; Zhang-Akiyama, Qiu-Mei; Ramotar, Dindial (Frontiers in Cell and Developmental Biology, 2020)
Exogenous and endogenous damage to the DNA is inevitable. Several DNA repair pathways are conserved across all organisms to faithfully maintain the integrity of the genome. The base excision repair (BER) pathway functions to repair single-base DNA lesions and in the process creates the premutagenic apurinic/apyrimidinic (AP) sites. In this review, we discuss the components of the BER pathway in the nematode Caenorhabditis elegans and delineate the different phenotypes caused by the deletion or the knockdown of the respective encoded gene, as well as the implications. To date, two DNA glycosylases have been identified in C. elegans, the monofunctional uracil DNA glycosylase-1 (UNG-1) and the bifunctional endonuclease III-1 (NTH-1) with associated AP lyase activity. In addition, the animal possesses two AP endonucleases belonging to the exonuclease-3 and endonuclease IV families and in C. elegans these enzymes are called EXO-3 and APN-1, respectively. In mammalian cells, the DNA polymerase, Pol beta, that is required to reinsert the correct bases for DNA repair synthesis is not found in the genome of C.elegans and the evidence indicates that this role could be substituted by DNA polymerase theta (POLQ), which is known to perform a function in the microhomology-mediated end-joining pathway in human cells. The phenotypes observed by the C. elegans mutant strains of the BER pathway raised many challenging questions including the possibility that the DNA glycosylases may have broader functional roles, as discuss in this review.